2022
DOI: 10.3390/ma15062265
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms and Dielectric Features of Mg-Doped ZnO Nanocrystals for Device Applications

Abstract: Magnesium-doped zinc oxide “ZnO:Mg” nanocrystals (NCs) were fabricated using a sol gel method. The Mg concentration impact on the structural, morphological, electrical, and dielectric characteristics of ZnO:Mg NCs were inspected. X-ray diffraction (XRD) patterns display the hexagonal wurtzite structure without any additional phase. TEM images revealed the nanometric size of the particles with a spherical-like shape. The electrical conductivity of the ZnO NCs, thermally activated, was found to be dependent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 65 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…The decrease in the dielectric constant with the increase in the frequency is due to contribution of the dipole, electronic, ionic polarization, and charge polarization. At higher frequency, the nano dipole fails to keep up with the speedy differences of electric field, and hence, it exhibits no dispersion with the electric field, resulting in exponential decay in the dielectric constant. , Moreover, the bulk WS 2 shows a very high dielectric constant of 7482373 at 100 Hz and ∼10000 at 2 MHz (Figure c). The results show an unusual trend, and despite increasing the dielectric constant, an extreme reduction of about 1426 times in the dielectric constant was observed for the WS 2 nanosheet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in the dielectric constant with the increase in the frequency is due to contribution of the dipole, electronic, ionic polarization, and charge polarization. At higher frequency, the nano dipole fails to keep up with the speedy differences of electric field, and hence, it exhibits no dispersion with the electric field, resulting in exponential decay in the dielectric constant. , Moreover, the bulk WS 2 shows a very high dielectric constant of 7482373 at 100 Hz and ∼10000 at 2 MHz (Figure c). The results show an unusual trend, and despite increasing the dielectric constant, an extreme reduction of about 1426 times in the dielectric constant was observed for the WS 2 nanosheet.…”
Section: Methodsmentioning
confidence: 99%
“…However, synthesis of the pure and crystalline WS 2 nanosheet is very crucial. Cao et al recently reported a lightweight and high-performance microwave absorber based on 2D WS 2 –RGO heterostructures synthesized via a facile one-step hydrothermal approach, which exhibited an effective absorption bandwidth due to the interfacial dielectric coupling effect. , They have also observed the synergetic dielectric loss and magnetic loss toward microwave absorption through hybridization of WS 2 nanosheets and NiO nanoparticles. , Heterostructures of Co 3 O 4 clusters–WS 2 nanosheets as efficient microwave absorption structures were also reported, and it has been shown that the dielectric property of the WS 2 played an important role in achieving the high efficiency of the devices. Moreover, to fabricate nanoscale devices such as LEDs, optoelectronic devices, and energy storage/generation devices, the tuning of the band gap and dielectric constant is urgently needed . However, the dielectric constant of pristine WS 2 nanosheets grown by the hydrothermal route is not yet reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The result shows a non-Debye-type relaxation for all samples. The deviation to a Debye profile in the current system could be attributed to the formation of macroscopic dipole groups and/or the formation of non-polar clusters [ 17 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The semicircles were well-fitted based on the expressions of both and : where R b and A b designed the resistive and capacitive components of the bulk region, respectively. R int and A int are the resistive and capacitive components of the interfacial impedance that correspondingly determine the space charge polarization [ 17 ]. The parameters n 1 and n 2 are the exponential indexes relatives to the bulk region and the interface.…”
Section: Results and Analysismentioning
confidence: 99%